Identifikasi Faktor-Faktor Pembiayaan Dalam Pelaksanaan Upacara Adat Kematian Rambu Solo’ Budaya Toraja - Jemi Pabisangan Tahirs; Rati Pundissing (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
ABSTRACT This study aims to identify the financing factors in the implementation of the Toraja culture of the traditional death ceremony (Rambu Solo '). The method used is descriptive qualitative. The results showed that the ritual of rambu solo 'was carried out in several stages, namely the stage of ceremony preparation (family gathering, making huts, provision of ceremony equipment) and ceremonial implementation stages (Ma'Pasulluk, Mangriu' Batu Messimbuang, Mebala'kan, Ma'Pasa '. Tedong, Ma'papengkalao, Lantang Mangisi, Ma'palao and Ma'pasonglo, Allo Katongkonan, Allo Katorroan, Mantaa Padang and Me Aa). This research concludes that the implementation of the rambu solo 'ceremony is different for each group (social strata). Keywords: Implementation cost, Social Strata, Toraja tribe